Radioinactive: Are nuclear power plant outages in France contagious to the German electricity price? - Sonja Rinne (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2018)
Are nuclear power plant outages in France contagious to the German electricity price? In the case of the extensive inspections from October 2016 to February 2017 in 12 French nuclear power plants: Yes. This capacity shock increased the French electricity spot market price by 14.15 Euros per MWh. The German-Austrian electricity spot market price was affected, with an increase of 1.72 Euros per MWh through cross-border trade. Hence, the current market integration between France and Germany to balance supply and demand in times of capacity shocks is limited. These results derive from a quasi-experimental approach based on coarsened exact matching. Thereby, the exogenous nature of the capacity shock is exploited as a random treatment in order to identify causal effects.
Keywords: C21; F15; L94; Q41; 330; electricity price; electricity trade; nuclear power; market integration